Australian multicentre study of current real‐world prophylaxis practice in severe and moderate haemophilia A and B. Issue 2 (3rd January 2018) - Mason, J. A.; Parikh, S.; Tran, H.; Rowell, J.; McRae, S.
Abstract : Introduction: With the emergence of novel treatment products for haemophilia and an increasing focus on the benefits of pharmacokinetic driven individualized prophylaxis, robust national data with regard to current patterns of factor consumption and adherence are required. Aim: To characterize current Australian practice with regard to use of prophylactic clotting factor infusions in patients with moderate or severe haemophilia A (HA) and haemophilia B (HB). Methods: This was a retrospective, non‐interventional study utilizing Australian Bleeding Disorder Registry (ABDR) data collected over a 12 month period. Registered and consented patients with moderate or severe HA or HB without inhibitors were included. Results: A total of 718 HA (551 severe, 167 moderate) and 166 HB (87 severe, 79 moderate) patients were included. Regular prophylaxis was prescribed in 453 patients (82%) with severe HA, 42 patients (25%) with moderate HA, 66 patients (75%) with severe HB and 11 patients (14%) with moderate HB. Near universal prophylaxis was achieved in the paediatric subgroup. The mean weekly dose of factor VIII in severe HA was 84 international units/kg/wk (IU/kg/wk) vs 71 IU/kg/wk of factor IX in severe HB. Most patients on prophylaxis were treated ≥3 times/wk (HA) or 2 times/wk (HB). Non‐adherence peaked in the 20‐29 year age group. Older individuals on regular prophylaxis used more factor than was expected for their prescribed regimen. Conclusion: Prophylaxis rates in severe haemophilia are comparable with other developed nations. The benefit of a national registry is demonstrable. Furthermore research into the underlying reasons for non‐compliance in young adults with haemophilia is required.